STUDI KOMPARATIF TAHAPAN PERENCANAAN PEMBANGUNAN PERDESAAN DI INDONESIA DAN MALAYSIA (Studi Kasus: Desa Alamendah, Kabupaten Bandung-Indonesia dan Desa Peruas, Pahang-Malaysia) - PANDU RAHARJO, AHLUNNAZA; KURNIASARI, NIA (Program Studi Perencanaan Wilayah Kota, 2014)
The growth of urban areas very rapidly raises significant issues that take effect in the development of rural areas. The strategic issues of rural development in Indonesia and Malaysia are poverty, unemployment, and economic vulnerability of rural communities; limited availability of public services and the minimum basic service, low empowerment of rural communities, not optimal village governance and institutional role of the village in the planning and development of the village, not optimal spatial arrangement of rural areas, natural resource management and environmental environment, the limited availability of infrastructure in the open isolation of rural areas and encourage linkages Rural- Urban.This study is intended to determine how the rural development planning process in Indonesia dan Malaysia. This study used qualitative research methods with a qualitative descriptive design format to describe the condition of the various phenomena that exist in the community that the object of research, and pull it to the surface of reality as a feature, character, nature, model or description of the condition or phenomenon particular. Data was collected through structured and in-depth interviews, and studies in the literature that focused on the exploration of related literature. Data analysis is done by using the method of triangulation and interpretative. Triangulation method rests on the validity of the findings and the level of confidence. Data analysis is inductive, meaning is the result of research rather than generalizations.Stages of Rural Development Planning in Indonesia and Malaysia are basically not much different, the two countries each have the characteristics and traits of its own in the formulation of rural development planning in the country. Based on the Minister Regulation Number 114 of 2014 on Guidelines for Rural Development, Indonesia defines the planning of rural development in the form of Mid Term Development Plan Rural (Rural Development Plan). Malaysia defines the rural development plan according to Act 172 About Design City and Village act 1976 in the form Slowly Rural (PTD). The results of this research can be used as a model for the analysis of policy makers both at the central and regional governments.